First Corinthians - Hays, Richard B (Louisville, Ky. John Knox Press, 1997)
Paul's first letter to the Corinthians was addressed originally to a fledgling mission church in Corinth. Paul's absence from the church had allowed serious problems to arise within the Corinthian community, but the problems that he addresses in this letter do not always seem based on explicitly theological ideas. The brilliance of Paul, though, is that he frames the issues in theological terms and reflects on them in the light of the gospel.
Includes bibliographical references (p. [297]-299)
Keywords: Bible. - Commentaries